Peran Sosial Kh Abdul Hadi Shofwan Pada Pendidikan Islam Di Temanggung Dalam Perspektif Sosiologi - Sabilla, Dheta Ari (Institut Islam Nahdlatul Ulama Temanggung, 2023)
KH Abdul Hadi Shofwan is a caregiver at the Mu'allimin Jampirejo Islamic Boarding School in East Temanggung, a political figure, organizer, and very concerned about the world of Islamic education. KH Abdul Hadi Shofwan apart from focusing on religious activities, he is also an activist in the organization and bureaucracy in Temanggung. His concern for the people of Temanggung, especially in the development of human resources, encouraged him to establish a formal school integrated with Islamic boarding schools. This research will discuss the biography and social role of KH Abdul Hadi Shofwan in Islamic education in Temanggung. This research uses descriptive qualitative research and uses historical and sociological approaches. In analyzing the facts about the social role of KH Abul Hadi Shofwan, towards Islamic education in Temanggung, the authors analyze it by using the role theory of Gross, Mason, and Mc. Eachern. The results of this study in general are, KH Abdul Hadi Shofwan's social role is part of a social process, namely the reciprocal influence between aspects of social life, namely occupying strategic positions in the bureaucracy and socio-religious organizations with aspects of religious life. with the Mualimin boarding school. This was manifested in its role in Islamic education in Temanggung at that time.